Decision Making Using AI in Energy and Sustainability Methods and Models for Policy and Practice - Kayakutlu, Gülgün; Kayalica, M. Özgür (Applied Innovation and Technology Management, 2023)
XI, 312 p. 83 illus., 77 illus. in color.